Efecto del Diagrama de Flujo en el rendimiento académico del Cálculo Integral en estudiantes de la Facultad de Ingeniería de Sistemas e Informática de la Universidad Nacional de la Amazonía Peruana Iquitos 2024 - Tuesta Moreno, Manuel (2025)
The purpose of this research is to evaluate the effect of the Flowchart on the academic performance of Integral Calculus in students of the Faculty of Systems Engineering and Computer Science of the National University of the Peruvian Amazon, Iquitos 2024. The problem is formulated in the following terms: What is the effect of the Flowchart on the academic performance of Integral Calculus in these students? As specific objectives, it is proposed to determine its effect on both conceptual and procedural learning. The study is framed within a quantitative approach, of an evaluative type and a quasi experimental design, with a control group and an experimental group, using non-probabilistic convenience sampling. The sample consisted of 49 students enrolled in the 2024-II semester, applying conceptual and procedural evaluation instruments validated by expert judgment. The results show significant differences between both groups after the intervention, with notable improvements in the conceptual and procedural learning achievements of the experimental group. It is concluded, with a probability of error of 0.025, that the use of the Flowchart significantly influences academic performance in Integral Calculus, validating the general and specific research hypotheses. Its implementation is recommended as a teaching strategy in the teaching of mathematics in higher education.